The Effects Of Sustainability Report Disclosures Towards Financial Performance Of Companies Listed In IDX80 - Triwacananingrum, Wijaya; Su, Sienish (Universitas Pamulang, 2023)
In an endeavour to develop sustainability, companies disclose sustainability reports as a practice of corporate responsibility practices towards social and environment, which oriented towards fulfilling public expectations for the existence of a business. This study aims to examine the effect of disclosing economic performance, environmental performance, and social performance in sustainability report on the financial performance of companies listed in the IDX80 stock index. Disclosures of sustainability report is measured using the GRI Standards Index. The independent variables in this study are disclosure of economic performance, disclosure of environmental performance, and disclosure of social performance. The dependent variable in this study is return on assets. This study is a quantitative study using a sample of 47 companies listed on the IDX80 stock index as the research object. The data collection method used is the documentation method of content analysis of sustainability reports and financial reports. The data analysis method used the multiple linear regression analysis method. The results show that the disclosure of economic performance, environmental performance, and social performance partially has no effect on the company’s financial performance.